Implementasi pendidikan akhlak dan moral perspektif kitab Al-Akhlaq Lil Banat pada siswi Thursina IIBS - Saputra, Moh. Aditya Hadi (Maliki Interdisciplinary Journal, 2024)
The moral decline in students is one of the impacts of the phenomenon of globalization. The facts circulating show that there is a drastic decline in the morals of youth, especially among women. One of the rampant cases is the decline in women’s morals that are not in accordance with Islamic values, even around fifty thousand underage girls have registered marriage with the religious affairs office on the grounds of being pregnant outside of marriage. Based on this reality, this study aims to implement morals and morals in accordance with Islamic religious values in female students through akhlaqul lil banat. The method used is library research on books, journals, and literature related to moral education and the book of akhlaqul lil banat. This research shows that students at Thursina International Islamic Boarding School are able to have morals and morals in accordance with the book of Al- Akhlaq lil Banat. Second, learning in the book of akhlaqul lil banat can provide a solution to the moral decline of the nation’s girls. Third, the relevance of learning the book of akhlaqul lil banat to Thursina International Islamic Boarding School students and their practice in everyday life.